A Review of the new initiatives at the NASA Ames Research Center : summary of a workshop - Wessner, Charles W. (Compass series (Washington, D.C.), 2001)
NASA Ames Research Center, in the heart of Silicon Valley, is embarking on a program to develop a science and technology park bringing together leading companies and universities to capitalize on Ames exceptional mission and location. Other initiatives under consideration include the integration of SBIR grants with a planned on-site incubator, virtual collaboration, and possibly a new public venture capital program. The STEP Board was asked by the NASA Administrator to hold a one-day symposium to review these initiatives. This report includes commissioned research papers and a summary of the proceedings of the symposium organized in response to the NASA request.